Redescription of the species of Anacroneuria Klapálek known from the Reserva Florestal Adolpho Ducke, Amazonas, Brazil with a neotype designation, and a key to adults males, Amazonas, Brazil. (Plecoptera, Perlidae) - Ribeiro, José Moacir Ferreira; Rafael, José Albertino (Zootaxa, 2009)
Three known species of Anacroneuria Klapálek,1909 from Reserva Florestal Adolpho Ducke (RFAD), Amazonas, Brazil are redescribed: A. minuta Klapálek, 1922 from the male; A. manauensis Ribeiro-Ferreira, 2001 from the Holotype male; A. marlieri Froehlich, 2001 from a Neotype male, herein designated. A fourth species is herein designated as putatively occurring in the RFAD, A. amazonica Froehlich, 2003, and is redescribed from a female paratype. A key to adults known to occur in RFAD is also presented.